India towards organic farming - Kumar, Dinesh (Indian Farming, 2021)
Organic farming reduces dependence on external farm inputs, reduces energy use, and increases agricultural income. Soil, water, air and environmental health improve by the adoption of organic farming. It further improves the soil’s internal and external biodiversity, which helps in improvement of soil health. Crop productivity is less in the few initial years. If suitable cropping methods and proper crop management are adopted in organic farming, then crop yield equals to or become higher than the conventional farming. It is necessary to adopt proper crop rotations and diversification to get good yields. Also, proper nutrient, pest- and disease-management are necessary. Organic farming can be successful adopted in certain areas, climates and conditions in India. With the increasing awareness of consumers about the safety and quality of organic foods, given the long-term sustainability of the farming system and the evidence of being equally productive, organic farming is going to be adopted by a greater number of farmers. The domestic, as well as international market of organic products has been growing quite rapidly in India. Looking at its economic, social, health and environmental benefits, it can be said that there is immense potential for its contribution to sustainable rural development in the country. A great opportunity for employment of rural youth exists in the production, processing and marketing of organic products and inputs. However, many types of obstacles are faced by farmers and other stakeholders in organic farming and it is also important to overcome them. It can be easily realized by looking at the number and interest of farmers in India that India is slowly but steadily moving towards organic farming.